Hydration of selenolate moiety Ab initio investigation of properties of O-H⋯Se(-) hydrogen bonds in CH3 Se(-)⋯(H2 O)n clusters - Karpov, Valerii V (Journal of computational chemistry, 2021)
© 2021 Wiley Periodicals LLC.